Composite sheet, inner container, cooking utensil and manufacturing method of composite sheet

By setting a groove on the surface of the metal substrate and filling the non -stick structure of fluorine resin, combined with the sedimentary coating of the physical gas phase, the problem of insufficient adhesion for the existing non -stick coating material is solved, and higher non -stick performance and hardness are achieved.

CN119326283APending Publication Date: 2025-01-21ZHEJIANG SUPOR ELECTRICAL APPLIANCES MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310883988.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The adhesion between the existing non-stick coating materials and the substrate is insufficient and it is easy to fall off under external forces. The defects in uniformity and curing conditions during the coating preparation process will lead to uneven or incomplete coatings.

Method used

A composite sheet design is adopted, in which multiple grooves are provided on the surface of the metal substrate. The coating is attached through physical vapor deposition, and the fluororesin non-stick structure is set in the grooves through mortise and tenon connections to form a hard coating and non-stick structure.

Benefits of technology

Significantly improves the non-stick performance and hardness, enhances the adhesion and durability of the non-stick structure, and reduces the wear of fluorine-containing resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326283A_ABST
    Figure CN119326283A_ABST
Patent Text Reader

Abstract

The invention discloses a composite sheet, an inner container, a cooking utensil and a manufacturing method of the composite sheet. The composite sheet comprises a metal matrix, a coating film and a non-stick structure. A plurality of grooves are formed in the surface of the metal base body, the coating film is attached to the surface of the metal base body through physical vapor deposition, the non-stick structure is made of fluorine-containing resin, the non-stick structure is arranged in the grooves and is in mortise and tenon connection with the inner wall faces of the grooves, and the surface of the non-stick structure is lower than the surface, located outside the grooves, of the metal base body. According to the composite sheet, the metal matrix is coated, so that the hard coating is formed on the surface of the metal matrix, the hardness and rigidity of a use surface are remarkably improved, and the composite sheet has certain non-stick performance. The groove is formed in the surface of the metal base body, the fluorine-containing resin is connected through the mortise and tenon structure, a non-stick structure is formed, the non-stick performance is further improved, and meanwhile abrasion to the fluorine-containing resin is reduced through the groove.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cooking utensils, and more specifically to a composite sheet, an inner pot, a cooking utensil, and a method for manufacturing the composite sheet. Background Art

[0002] Materials with non-stick properties are usually provided with a non-stick coating on the substrate, but the existing coating materials do not have strong enough adhesion to the substrate, and the coating is easy to fall off after being scratched, squeezed or stretched. During the coating preparation process, if there are defects in the uniformity of material coating, curing conditions, etc., it may cause uneven or incomplete coating, making the coating easy to fall off.

[0003] Therefore, there is a need for a composite sheet, an inner pot, a cooking utensil and a method for manufacturing the composite sheet to at least partially solve the above problems. Summary of the invention

[0004] A series of simplified concepts are introduced in the Summary of the Invention section, which will be further described in detail in the Detailed Description of the Invention section. The Summary of the Invention section of this application does not mean to attempt to define the key features and essential technical features of the claimed technical solution, nor does it mean to attempt to determine the scope of protection of the claimed technical solution.

[0005] In order to at least partially solve the above problems, the present application provides a composite sheet, comprising:

[0006] A metal substrate, wherein a plurality of grooves are arranged on the surface of the metal substrate;

[0007] A coating, wherein the coating is attached to the surface of the metal substrate by physical vapor deposition;

[0008] A non-stick structure is made of fluorine-containing resin, is arranged in the groove and forms a mortise and tenon connection with the inner wall surface of the groove, and the surface of the non-stick structure is lower than the surface of the metal substrate outside the groove.

[0009] According to the composite sheet of the present application, a film is plated on the metal substrate so that a hard coating is formed on the surface of the metal substrate, thereby significantly increasing the hardness and rigidity of the use surface and having a certain non-stick property. A groove is provided on the surface of the metal substrate, and a fluorine-containing resin is provided through a mortise and tenon structure to form a non-stick structure, further improving the non-stick property. At the same time, the groove setting reduces the wear of the fluorine-containing resin. The non-stick structure provided by the present application has high strength, excellent non-stick property, firm connection and durability.

[0010] Optionally, the transverse cross-sectional area of ​​the bottom of the groove is larger than the transverse cross-sectional area of ​​the top of the groove. According to this solution, a structure with a large internal space and a small opening can be formed, and the non-stick structure filled in the groove is not easy to fall off.

[0011] Optionally, the transverse cross-sectional area of ​​the groove gradually decreases in a direction away from the bottom of the groove. The groove has a smooth inner wall surface, which is convenient for processing and forming the groove.

[0012] Optionally, the groove includes a straight tube portion and a mortise and tenon portion, wherein the transverse cross-sectional area of ​​the straight tube portion is less than or equal to the transverse cross-sectional area of ​​the mortise and tenon portion, and the transverse cross-sectional area of ​​the mortise and tenon portion gradually decreases in a direction away from the bottom of the groove. According to the above arrangement, the inner wall surface of the groove has a smooth transition, which is convenient for the molding process of the groove and also convenient for filling with fluorine-containing resin.

[0013] Optionally, a longitudinal cross-section of the groove is at least partially trapezoidal in shape.

[0014] Optionally, the transverse cross-section of the groove is circular or polygonal, thereby improving the aesthetics of the composite sheet.

[0015] Optionally, the radial dimension of the top opening of the groove is 0.1-9 mm, and / or the radial dimension of the bottom of the groove is 0.2-10 mm. The size range is reasonable.

[0016] Optionally, the depth of the groove is 0.01 mm-10 mm, and / or the surface roughness of the metal substrate is 0.1-3 μm.

[0017] Optionally, the surface of the non-stick structure is configured as a downwardly concave arc surface, thereby reducing wear on the non-stick structure.

[0018] Optionally, the total surface area of ​​the non-stick structure accounts for 10%-50% of the surface area of ​​the composite sheet, thereby balancing non-stickiness and durability and providing a better use experience.

[0019] Optionally, the non-stick structure is made of PFA and / or PTFE, which has excellent non-stick, chemical resistance and high temperature resistance.

[0020] Optionally, the coating includes:

[0021] A bottom layer, the bottom layer is attached to the metal substrate, and the bottom layer is a metal layer;

[0022] A transition layer, wherein the transition layer is attached to the bottom layer, the transition layer comprises a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked;

[0023] The surface layer is attached to the transition layer, and the surface layer is constructed as a columnar nano-crystal structure layer grown by physical vapor deposition.

[0024] Optionally, the bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer. According to the above configuration, the metal bottom layer can increase the bonding force between the coating and the metal substrate, making it difficult for the coating to fall off from the metal substrate, thereby increasing the service life.

[0025] Optionally, the first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;

[0026] The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;

[0027] The second transition layer is different from the first transition layer. According to the above configuration, the transition layer formed by alternating two material layers formed by titanium, chromium and zirconium base and their compounds can produce a template effect on the growth of the columnar nanocrystalline structure, causing lattice distortion, inhibiting the growth of coarse columnar nanocrystals on the surface, and making the columnar grains tend to grow vertically to the crystal plane, thereby reducing the surface energy of the surface layer, forming a small and dense columnar nanocrystalline structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the surface layer becomes denser, its hardness and corrosion resistance are also improved.

[0028] Optionally, the columnar nanocrystalline structure in the surface layer has a plurality of crystal grains growing in a columnar shape, the side surfaces of the plurality of crystal grains are bonded to each other, and when the surface layer is at a predetermined thickness, the top ends of the crystal grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure. According to this solution, the surface of the coating forms a nano-scale concave-convex structure, which improves the non-stickiness and easy cleaning properties.

[0029] Optionally, the radial size of the grains is 20-80 nm; and / or

[0030] The predetermined thickness of the surface layer is 100-600 nm. According to this solution, a nanometer scale can be provided for the surface of the coating to form a special columnar nano crystal structure.

[0031] Optionally, the surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer. According to the above configuration, the specific surface layer material can enable the surface layer to grow into a columnar nanocrystalline structure, further improving the non-stickiness and easy-to-clean properties of the composite sheet.

[0032] Optionally, the surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer, and the amorphous copper is coated outside the grains of the columnar nanocrystalline structure. According to this solution, the surface of the coating can be provided with a nanoscale scale to form a special columnar nanocrystalline structure.

[0033] Optionally, the surface of the metal substrate includes a first surface located in the groove and a second surface located outside the groove, and the coating includes a first coating attached to the first surface and a second coating attached to the second surface, wherein the thickness of the second coating is greater than the thickness of the first coating. The second coating is thickened to improve its wear resistance, thereby protecting the metal substrate.

[0034] Optionally, the thickness of the second coating is 500-5000nm, and / or

[0035] The thickness of the first coating is 500-2000 nm. The coating thickness is reasonably set and is easy to combine with the metal substrate.

[0036] A second aspect of the present application provides an inner liner, which is made of the composite sheet material described in the first aspect.

[0037] The inner liner according to the present application is made of the composite sheet material described in the first aspect above, and therefore has a technical effect similar to that of the composite sheet material of the first aspect above.

[0038] A third aspect of the present application is a cooking utensil, comprising the inner pot described in the second aspect.

[0039] The cooking utensil according to the present application has the inner pot of the second aspect, and thus has a technical effect similar to that of the inner pot of the second aspect.

[0040] A fourth aspect of the present application provides a method for manufacturing a composite sheet, the method comprising:

[0041] A step of preparing a metal substrate, wherein the step of preparing a metal substrate comprises a step of forming grooves, wherein a plurality of grooves are formed by etching the surface of the metal substrate;

[0042] A physical vapor deposition step of depositing a coating on the surface of the metal substrate;

[0043] The groove filling step is to fill the groove with a fluorine-containing resin to form a non-stick structure.

[0044] According to the manufacturing method of the composite sheet of the present application, a groove can be opened in the metal substrate, and a non-stick structure is arranged in the groove to enhance the non-stick performance of the composite sheet and improve the adhesion of the non-stick structure.

[0045] Optionally, the groove is formed by using one of an electrochemical etching process, a chemical etching process, and a laser etching process.

[0046] Optionally, the step of preparing the metal substrate further comprises a first polishing step after the step of forming the grooves, wherein the metal substrate is treated by mechanical polishing, plasma polishing, magnetic fluid polishing or chemical polishing, so that the surface of the metal substrate to be coated has a roughness of 0.1-3 μm. According to the above configuration, the relatively smooth surface of the metal substrate can make the coating surface also have smooth characteristics, which is conducive to improving hydrophobicity, non-stickiness and easy cleaning.

[0047] Optionally, the groove filling step also includes: filling the fluorine-containing resin into the groove using an impregnation process, an injection molding process, an electrostatic spraying process or a compressed air spraying process, and treating the metal substrate at a temperature of 350-450°C after filling so that the fluorine-containing resin in the groove is leveled and fills the groove.

[0048] Optionally, the groove filling step further includes a second polishing step: removing the fluorine-containing resin on the metal substrate outside the groove by mechanical polishing to expose the coating outside the groove, and making the surface of the non-stick structure lower than the surface of the coating outside the groove.

[0049] Optionally, the physical vapor deposition step includes a surface deposition step: the surface layer of the coating is grown into a columnar nanocrystalline structure by physical vapor deposition. According to the above process, a coating having a columnar nanocrystalline structure can be deposited on the surface of a metal substrate, and the coating has high hardness, high adhesion, high non-stickiness and easy cleaning.

[0050] Optionally, a deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source;

[0051] The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis;

[0052] The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening a carbon source and a nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer. According to the above arrangement, a columnar nanocrystalline surface layer of carbonitride can be grown on the surface of the metal substrate by the PVD process.

[0053] Optionally, the physical vapor deposition step further includes a transition layer deposition step, the transition layer deposition step is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing a first transition layer and a second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal element of the first metal target reacts with the carbon source and the nitrogen source to form the first transition layer, and the metal element of the second metal target reacts with the carbon source and the nitrogen source to form the second transition layer. According to the above process, the metal substrate is alternately covered by the coating material produced by the first metal target and the second metal target by rotation, so that the alternating first transition layer and the second transition layer can be efficiently formed.

[0054] Optionally, the physical vapor deposition step further includes a bottom layer deposition step, which is located before the transition layer deposition step, and the bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing the metal bottom layer on the surface to be deposited of the metal substrate. According to the above configuration, the metal bottom layer can be deposited using the same PVD equipment, and the metal bottom layer can increase the bonding force between the coating and the metal substrate, so that the coating is not easy to fall off from the metal substrate, thereby increasing the service life.

[0055] Optionally, the carbon source is acetylene gas, and the nitrogen source is nitrogen gas;

[0056] The step of depositing the surface layer also includes: setting the volume ratio of nitrogen to acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, and applying a bias voltage of 140-160V to the metal substrate during deposition. According to the above settings, a surface layer with a specific thickness can be obtained through specific process parameters, further improving the hardness, bonding strength and easy cleaning of the coating.

[0057] Optionally, the carbon source is acetylene gas, and the nitrogen source is nitrogen gas;

[0058] The step of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260° C., setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, and applying a bias voltage of 140-160 V to the metal substrate during deposition. According to the above settings, the hardness, bonding strength and easy cleaning of the coating can be further improved through specific process parameters.

[0059] Optionally, the step of depositing the bottom layer further comprises: setting the temperature of the deposition furnace to 200-450° C., glow cleaning the metal substrate for 3-7 minutes before deposition, and applying a bias voltage of 50-250 V to the metal substrate during deposition. According to the above settings, a bottom layer with specific parameters can be obtained through specific process parameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] The following drawings of the present application are used as a part of the present application for understanding the present application. The drawings show the embodiments of the present application and their descriptions, which are used to explain the principle of the present application.

[0061] In the attached figure:

[0062] Figure 1 A schematic diagram of a composite sheet coating structure according to an embodiment of the present application;

[0063] Figure 2 is a schematic diagram of a metal substrate structure according to an embodiment of the present application;

[0064] Figure 3 It is an enlarged schematic diagram of composite sheet coating according to one embodiment of the present application;

[0065] Figure 4 A schematic diagram of a composite sheet application according to an embodiment of the present application;

[0066] Figure 5 is a schematic cross-sectional view of a composite sheet according to one embodiment of the present application;

[0067] Figure 6 A more detailed schematic cross-sectional structure diagram of a coating of a composite sheet according to an embodiment of the present application;

[0068] Figure 7a-7d It is a schematic diagram of the cross-sectional structure of the surface layer of the coating according to the present application at different growth thicknesses;

[0069] Figure 8 is a top cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;

[0070] Fig. 9 is a side cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;

[0071] Fig.10 A simplified flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application;

[0072] Fig.11 A more detailed schematic flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application. DETAILED DESCRIPTION

[0073] In the following description, a large number of specific details are provided to provide a more thorough understanding of the present application. However, it is apparent to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features well known in the art are not described.

[0074] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of the features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or combinations thereof.

[0075] Ordinal numbers such as "first" and "second" cited in this application are merely identifiers and do not have any other meaning, such as a specific order. Moreover, for example, the term "first component" itself does not imply the existence of a "second component", and the term "second component" itself does not imply the existence of a "first component". It should be noted that the terms "upper", "lower", "front", "back", "left", "right", "inner", "outer" and similar expressions used in this document are for illustrative purposes only and are not limiting.

[0076] Now, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings.

[0077] refer to Figure 1-Figure 2 In the first aspect of the present application, there is provided a composite sheet, comprising a metal substrate 110, a coating and a non-stick structure 200. The metal substrate 110 may be made of, for example, stainless steel, titanium, titanium alloy, aluminum alloy or the like. A plurality of grooves 100 are provided on the surface of the metal substrate 110. The coating is attached to the surface of the metal substrate 110 by physical vapor deposition. The non-stick structure 200 is made of a fluorine-containing resin, the non-stick structure 200 is disposed in the groove 100 and forms a mortise and tenon connection with the inner wall surface of the groove 100, and the surface of the non-stick structure 200 is lower than the surface of the metal substrate 110 outside the groove 100. According to this solution, the fluorine-containing resin is connected to the groove 100 of the metal substrate 110 by mortise and tenon.

[0078] According to the composite sheet of the present application, the connection strength between the fluorine-containing resin and the metal matrix 110 is enhanced, making the connection more firm and durable, and increasing the rigidity and stability of the overall structure. The solidified fluorine-containing resin is filled in the groove 100 of the metal matrix 110, which can disperse the stress and reduce the local stress concentration, thereby preventing the occurrence of cracks and breakage; at the same time, the fluorine-containing resin has good non-stickiness, heat resistance and chemical corrosion resistance, so that the composite sheet has non-stickiness and is strong and durable.

[0079] The transverse cross-sectional area of ​​the bottom of the groove 100 is greater than the transverse cross-sectional area of ​​the top of the groove 100. In the present application, the transverse direction D1 is a direction parallel to the surface of the metal substrate 110 where the groove 100 is opened. According to this solution, a structure with a large internal space and a small opening can be formed, the non-stick structure 200 is filled in the groove 100 and is not easy to fall off, the non-stick structure 200 is stably connected to the metal substrate 110, and the non-stick structure 200 can provide additional support and reinforcement to enhance the structural strength of the composite sheet.

[0080] The transverse cross-sectional area of ​​the groove 100 gradually decreases in a direction away from the bottom of the groove 100. The groove 100 has a smooth inner wall surface, which facilitates the processing and forming of the groove 100.

[0081] For example, Figure 3 As shown, the groove 100 includes a straight tube portion and a mortise and tenon portion, wherein the transverse cross-sectional area of ​​the straight tube portion is less than or equal to the transverse cross-sectional area of ​​the mortise and tenon portion, and the transverse cross-sectional area of ​​the mortise and tenon portion gradually decreases in the direction away from the bottom of the groove 100. It can be understood that at the connection between the straight tube portion and the mortise and tenon portion, the transverse cross-sectional area of ​​the straight tube portion is equal to the transverse cross-sectional area of ​​the mortise and tenon portion. The inner wall surface of the groove 100 has a smooth transition, which is convenient for the processing of the groove 100 and also for the filling of the fluorine-containing resin. The shape of the longitudinal cross-section of the groove 100 is at least partially constructed as a trapezoid. In the present application, the longitudinal direction D2 is the direction perpendicular to the surface of the metal substrate 110 where the groove 100 is opened.

[0082] like Figure 4 As shown, the transverse cross-section of the groove 100 is circular or polygonal in shape. The outer edge of the groove 100 is a part of the exposed surface of the composite sheet, and the overall aesthetics is improved by setting a circular or polygonal regular shape.

[0083] The radial dimension of the top opening of the groove 100 is 0.1-9 mm, and / or the radial dimension of the bottom of the groove 100 is 0.2-10 mm. Within the size range provided in this embodiment, the groove 100 is easy to form, the filling amount of the fluorine-containing resin is reasonable, and the groove 100 of the metal substrate 110 is easy to combine with the fluorine-containing resin to form a high-strength structure. The depth of the groove 100 is 0.01 mm-10 mm. Within the size range provided in this embodiment, the fluorine-containing resin is easier to fill in the groove 100, and the groove 100 of the metal substrate 110 is easy to combine with the fluorine-containing resin to form a high-strength structure. The surface roughness of the metal substrate 110 is 0.1-3 μm. The relatively smooth surface of the metal substrate 110 can make the coating surface also have smooth characteristics, which is conducive to improving hydrophobicity, non-stickiness and easy cleaning; a reasonable roughness range can further improve the bonding force between the metal substrate 110 and the coating 150.

[0084] The surface of the non-stick structure 200 is a concave arc surface. The composite sheet of this embodiment is used to prepare cooking pots, which can reduce the direct contact area between food and the metal substrate, making it easier to slide and flip, and improving the non-stick effect. The non-stick structure 200 with lower mechanical strength is concave under the metal substrate with higher mechanical strength, which can effectively reduce the wear of the non-stick structure 200 during use.

[0085] The total surface area of ​​the non-stick structure accounts for 10%-50% of the surface area of ​​the composite sheet. Non-stick materials usually have relatively poor thermal conductivity. Too high a ratio will reduce the thermal conductivity of the entire pot and affect the cooking effect. Properly controlling the ratio can maintain good thermal conductivity of the pot and allow food to be heated evenly. Balance non-stickiness and durability through ratio control to provide a better user experience.

[0086] Exemplarily, the non-stick structure 200 is made of PFA and / or PTFE. PFA is polyperfluoroethylene, which has excellent non-stick properties, chemical resistance, and high temperature resistance. PTFE is polytetrafluoroethylene, which has excellent non-stick properties, chemical resistance, and high temperature resistance, and has a low friction coefficient, reducing friction and wear without using lubricating oil or grease. PFA and PTFE can be combined together to form a composite material by chemical methods or physical methods.

[0087] In some embodiments of the present application, the specific structure of the coating 150 is shown in Figure 5 and Figure 6The coating 150 includes a bottom layer 140, a transition layer 130 and a surface layer 120. The bottom layer 140 is attached to the surface of the metal substrate 110 by physical vapor deposition, the transition layer 130 is attached to the surface of the bottom layer 140 by physical vapor deposition, and the surface layer 120 is attached to the surface of the transition layer 130 by physical vapor deposition. In addition, the above-mentioned grains 121 grow in a direction perpendicular to the surface of the transition layer 130.

[0088] The bottom layer 140 is a metal layer, so that there is a strong bonding force between the metal bottom layer 140 and the metal substrate 110. Exemplarily, the bottom layer 140 can be a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer.

[0089] The transition layer 130 includes a first transition layer 131 and a second transition layer 132, and the first transition layer 131 and the second transition layer 132 are alternately stacked. The first transition layer 131 and the second transition layer 132 can both be selected from one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer, but the second transition layer 132 needs to be different from the first transition layer 131.

[0090] The surface layer 120 may be a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer. The specific material of the surface layer 120 and / or the thickness of the surface layer 120 can enable the surface layer 120 to grow into a columnar nanocrystalline structure, further improving the non-stickiness and easy-to-clean properties of the composite sheet. For example, the thickness of the surface layer 120 is preferably set to 100-600nm. When the thickness of the surface layer 120 is within the above-mentioned predetermined thickness range, a protrusion can grow on the top of the grain 121, so that the surface of the surface layer 120 forms a nano-scale concave-convex structure.

[0091] The columnar nanocrystalline structure in the surface layer 120 has a plurality of crystal grains 121 growing in a columnar shape, the side surfaces of the plurality of crystal grains 121 are attached to each other, and the radial dimension D of the crystal grains 121 is 20-80nm. According to this solution, the surface of the coating 150 can be provided with a nanoscale dimension to form a special columnar nanocrystalline structure.

[0092] The above-mentioned nanoscale refers to a scale ranging from 1 to 100 nm.

[0093] refer to Figure 7a-7d The cross-sectional morphology of the surface layer 120 at different growth thicknesses is shown. Figure 7a The cross-sectional morphology is shown when the thickness of the surface layer 120 is 50 nm. Figure 7b The cross-sectional morphology when the thickness of the surface layer 120 is 100 nm is shown. Figure 7c The cross-sectional morphology is shown when the thickness of the surface layer 120 is 400 nm. Figure 7dThe cross-sectional morphology when the thickness of the surface layer 120 is 600nm is shown. It can be seen from the figure that when the thickness of the surface layer 120 is 50nm, the top of the grain 121 cannot grow a protrusion 122, and the surface of the surface layer 120 forms a flat surface. As the deposition thickness of the surface layer 120 increases, when the thickness is greater than 100nm as shown in the figure, the top of the grain 121 gradually grows a protrusion 122, and the protrusion 122 becomes more obvious and fuller as the deposition thickness increases. However, when the deposition thickness of the surface layer 120 increases from 400nm to 600nm, the protrusion 122 at the top of the grain 121 tends to be flattened. It can be seen that when the deposition thickness of the surface layer 120 exceeds 600nm, if the protrusion 122 at the top of the grain 121 continues to be flat, the concave-convex structure will become less obvious.

[0094] In addition, the transition layer 130, which is an alternating arrangement of two material layers formed by titanium, chromium and zirconium base and their compounds, can produce a template effect on the growth of the columnar nanocrystalline structure of the surface layer 120, causing it to undergo lattice distortion, thereby inhibiting the growth of coarse columnar nanocrystals in the surface layer 120, and causing the columnar grains 121 to tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer 120 and forming a fine and dense columnar nanocrystalline structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the density of the surface layer 120 increases, its hardness and corrosion resistance also increase.

[0095] For example, as a first optional embodiment, the surface layer 120 is a titanium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a titanium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-titanium composite metal layer. As a second optional embodiment, the surface layer 120 is a zirconium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-zirconium composite metal layer. As a third optional embodiment, the surface layer 120 is a chromium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a titanium carbonitride layer, and the bottom layer 140 is a titanium-zirconium composite metal layer.

[0096] In order to further improve the bonding force between the surface layer 120 and the transition layer 130, the surface layer 120 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the surface layer 120 contain the same carbon nitride compound, for example, refer to the first optional embodiment and the second optional embodiment described above. In order to further improve the bonding force between the transition layer 130 and the bottom layer 140, the bottom layer 140 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the bottom layer 140 contain the same metal element, for example, refer to the first optional embodiment and the third optional embodiment described above.

[0097] In addition, copper can be added to the surface layer 120 to further improve the non-stick performance. That is, the surface layer 120 is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer. Since copper does not react with elements such as carbon and nitrogen, and cannot form a solid solution with carbonitrides, the copper added to the carbonitride will exist in an amorphous form, thereby forming a structure in which amorphous copper is coated outside the grains 121 of the columnar nanocrystalline structure. Such a structural form can further inhibit the growth of the grains 121, can form a finer grain structure, and effectively reduce the surface energy.

[0098] In this case, the optional combination of each layer can be: as a fourth optional embodiment, the surface layer 120 adopts a titanium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a fifth optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a sixth optional embodiment, the surface layer 120 adopts a zirconium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-zirconium composite metal layer. As a seventh optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a titanium carbonitride layer, respectively, and the bottom layer 140 adopts a titanium-zirconium composite metal layer.

[0099] In some embodiments of the present application, the surface of the metal substrate 110 includes a first surface 111 located in the groove 100 and a second surface 112 located outside the groove 100, and the coating 150 includes a first coating 151 attached to the first surface 111 and a second coating 152 attached to the second surface 112, wherein the thickness of the second coating 152 is greater than the thickness of the first coating 151. The second coating 152 is an exposed surface of the metal substrate 110, which bears more wear, and the second coating 152 is thickened to improve its wear resistance, thereby protecting the metal substrate.

[0100] The thickness of the second coating film 152 is 500-5000 nm. Within the size range provided in this embodiment, the coating film thickness is reasonably set and is easy to be combined with the metal substrate 110.

[0101] The thickness of the first coating film 151 is 500-2000 nm. Within the size range provided in this embodiment, the coating film thickness is reasonably set and is easy to be combined with the metal substrate 110 and the fluorine-containing resin.

[0102] The second aspect of the present application provides an inner liner, which is made of the composite sheet material of the first aspect. The inner surface of the inner liner is provided with the above-mentioned coating 150, so that the surface layer 120 of the coating 150 faces inward. Optionally, the outer surface of the inner liner can also be provided with the above-mentioned coating 150, and the surface layer 120 of the coating 150 faces outward. According to the inner liner of the present application, it is made of the composite sheet material of the first aspect, and therefore has a technical effect similar to that of the composite sheet material of the first aspect.

[0103] The third aspect of the present application is a cooking utensil, the cooking utensil comprising the inner pot of the second aspect. The cooking utensil according to the present application has the inner pot of the second aspect, and thus has a similar technical effect as the inner pot of the second aspect.

[0104] The fourth aspect of the present application provides a method for manufacturing a composite sheet, referring to Fig.10 and Fig.11 , a method for manufacturing a composite sheet, comprising:

[0105] Preparing a metal substrate step S1: The preparing a metal substrate step includes a groove forming step, wherein a plurality of grooves 100 are formed by etching the surface of a metal substrate 110;

[0106] Physical vapor deposition step S2: depositing a coating on the surface of the metal substrate 110;

[0107] The groove filling step S3 is to fill the groove 100 with a fluorine-containing resin to form a non-stick structure 200 .

[0108] According to the manufacturing method of the composite sheet of the present application, a coating is deposited on the surface of the metal substrate 110 by physical vapor deposition, which can produce a uniform hard film layer, so that the coating is evenly and uniformly distributed on the surface of the metal substrate 110. The non-stick property of the composite sheet is enhanced by filling with fluorine-containing resin.

[0109] Specifically, the step S1 of preparing the metal substrate includes:

[0110] Cleaning step S11: cleaning, degreasing and degreasing the metal substrate 110 .

[0111] Groove forming step S12: Groove 100 is formed on the metal surface by etching. Etching can achieve highly precise control, can accurately remove the required part, and avoid unnecessary waste. Specifically, the surface of the metal substrate 110 is etched to form the groove 100 by one of an electrochemical etching process, a chemical etching process, and a laser etching process. The etching process provides design freedom, and the shape, size, and depth of the groove 100 can be flexibly adjusted and optimized as needed. Compared with mechanical processing, these etching processes usually do not cause mechanical deformation or stress accumulation of the material. Moreover, the physical and chemical properties of the metal substrate 110 are less affected, and the original properties of the material are maintained.

[0112] The first polishing step S13: The metal substrate 110 is treated by mechanical polishing, plasma polishing, magnetic fluid polishing or chemical polishing. The defects such as tiny depressions, cracks, oxides and other contaminants on the surface of the metal substrate 110 can be removed by polishing, and the surface flatness and finish can be improved. This helps to reduce the presence of defects and contaminants in the subsequent physical vapor deposition process, improve the quality and performance of the coating, increase the contact area and bonding force between the coating and the metal substrate 110, and improve the adhesion, wear resistance and sealing of the coating. In this embodiment, the surface of the metal substrate 110 to be coated has a roughness of 0.1-3μm by polishing. Within the roughness range provided in this embodiment, the coating can be better bonded to the surface of the metal substrate 110.

[0113] The physical vapor deposition step S2 also includes a transition layer deposition step S22 and a bottom layer deposition step S21. The transition layer deposition step S22 is located before the surface layer deposition step S23, and the bottom layer deposition step S21 is located before the transition layer deposition step S22. In other words, in the physical vapor deposition step S2, the bottom layer 140 is deposited first, the transition layer 130 is deposited, and finally the surface layer 120 is deposited.

[0114] Among them, reference Figure 8 and Fig. 9 The deposition furnace 11 of the physical vapor deposition device 10 is provided with a rotating frame 12, a first metal target 13 and a second metal target 14, and the second metal target 14 is different from the first metal target 13. The first metal target 13 and the second metal target 14 are arranged at intervals around the rotation axis of the rotating frame 12, and the metal elements of the first metal target 13 and the second metal target 14 are selected from titanium, chromium or zirconium. For example, the first metal target 13 can be a titanium target, and the second metal target 14 can be a chromium target. The physical vapor deposition device 10 also has a carbon source and a nitrogen source, wherein the carbon source is acetylene gas and the nitrogen source is nitrogen gas.

[0115] Specifically, the physical vapor deposition step S2 includes:

[0116] In the step S21 of depositing the bottom layer, the first metal target 13 and / or the second metal target 14 are turned on, the nitrogen source and the carbon source are turned off, argon gas is continuously introduced into the deposition furnace 11, and the metal bottom layer 140 is deposited on the surface to be deposited of the metal substrate 110. This solution can use the same PVD equipment to deposit the metal bottom layer 140. More specifically, the step of depositing the bottom layer also includes: setting the temperature of the deposition furnace 11 to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate 110 during deposition, and depositing for a certain time to obtain a bottom layer 140 of a predetermined thickness.

[0117] In the step S22 of depositing the transition layer, the first metal target 13 and the second metal target 14 are opened, and the first transition layer 131 and the second transition layer 132 are alternately deposited on the surface to be deposited of the metal substrate 110 by rotation, wherein the metal element of the first metal target 13 reacts with the carbon source and the nitrogen source to form the first transition layer 131, and the metal element of the second metal target 14 reacts with the carbon source and the nitrogen source to form the second transition layer 132. According to the above process, the metal substrate 110 is alternately covered by the coating material produced by the first metal target 13 and the second metal target 14 by rotation, so that the first transition layer 131 and the second transition layer 132 alternately stacked can be efficiently formed. More specifically, the step of depositing the transition layer also includes: setting the temperature of the deposition furnace 11 to 240-260° C., setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for a certain time to obtain a transition layer of a predetermined thickness.

[0118] The surface layer deposition step S23 opens one of the first metal target 13 and the second metal target 14, opens the carbon source and the nitrogen source, and deposits the surface layer 120 on the surface to be deposited of the metal substrate 110, wherein the metal element of the first metal target 13 or the second metal target 14 reacts with the carbon source and the nitrogen source to form the surface layer 120. More specifically, the surface layer deposition step also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace 11 to 280-300°C, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for 10-30min to control the thickness of the surface layer 120 to be 100-600nm.

[0119] In the above-mentioned physical vapor deposition step S2, the rotation speed of the rotating frame 12 is set to 0.5-3 rpm to more effectively control the thickness of the coating 150 and make the thickness distribution of the coating 150 uniform. Specifically, the groove filling step S3 includes:

[0120] Step S31 of filling the groove: the fluorine-containing resin is filled into the groove 100 by an impregnation process, an injection molding process, an electrostatic spraying process or a compressed air spraying process, and the metal substrate 110 is treated at a temperature of 350-450° C. after filling, so that the fluorine-containing resin in the groove 100 is leveled and fills the groove 100. These processes can effectively fill the fluorine-containing resin into the groove 100, and make it leveled and fill the groove 100 by high temperature treatment. In this way, the groove 100 can be completely filled, and the sealing and chemical resistance of the groove 100 are improved. The fluorine-containing resin filled into the groove 100 forms a uniform, dense, wear-resistant coating, providing good sealing and protection.

[0121] Second polishing step S32: Remove the fluorine-containing resin on the metal substrate 110 outside the groove 100 by mechanical polishing to expose the coating outside the groove 100, and make the surface of the non-stick structure 200 lower than the surface of the coating outside the groove 100. The second mechanical polishing after filling the groove 100 can remove the excess fluorine-containing resin coating on the metal substrate 110 outside the groove 100, expose the coating outside the groove 100, ensure that the fluorine-containing resin coating inside the groove 100 is seamlessly connected with the coating outside the groove 100, and prevent the formation of cracks and defects between the coatings. Mechanical polishing can further improve the flatness and finish of the metal substrate 110 outside the groove 100.

[0122] The processes and steps in all the above preferred embodiments are only examples. Unless adverse effects occur, various processing operations can be performed in a sequence different from the sequence of the above processes. The sequence of steps in the above processes can also be increased, merged or deleted according to actual needs.

[0123] Unless otherwise defined, the technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein are only for describing specific implementation purposes and are not intended to limit the present application. The features described herein in one embodiment may be applied to another embodiment individually or in combination with other features, unless the feature is not applicable or otherwise specified in the other embodiment.

[0124] The present application has been illustrated through the above-mentioned embodiments, but it should be understood that the above-mentioned embodiments are only for the purpose of example and explanation, and the present application is not limited to the above-mentioned embodiments. According to the teachings of the present application, more variations and modifications can be made, and these variations and modifications all fall within the scope of protection claimed by the present application.

Claims

1. A composite sheet, characterized in that: include: A metal substrate, wherein a plurality of grooves are arranged on the surface of the metal substrate; A coating, wherein the coating is attached to the surface of the metal substrate by physical vapor deposition; A non-stick structure is made of fluorine-containing resin, is arranged in the groove and forms a mortise and tenon connection with the inner wall surface of the groove, and the surface of the non-stick structure is lower than the surface of the metal substrate outside the groove.

2. The composite sheet according to claim 1, characterized in that: The transverse cross-sectional area of ​​the bottom of the groove is greater than the transverse cross-sectional area of ​​the top of the groove.

3. The composite sheet according to claim 2, characterized in that: The transverse cross-sectional area of ​​the groove gradually decreases in a direction away from the bottom of the groove.

4. The composite sheet according to claim 2, characterized in that: The groove includes a straight tube portion and a mortise and tenon portion, wherein the transverse cross-sectional area of ​​the straight tube portion is less than or equal to the transverse cross-sectional area of ​​the mortise and tenon portion, and the transverse cross-sectional area of ​​the mortise and tenon portion gradually decreases in a direction away from the bottom of the groove.

5. The composite sheet according to claim 1, characterized in that: A longitudinal cross-section of the groove is at least partially configured as a trapezoid.

6. The composite sheet according to claim 1, characterized in that: The transverse cross-section of the groove is circular or polygonal in shape.

7. The composite sheet according to claim 2, characterized in that: The radial dimension of the top opening of the groove is 0.1-9 mm, and / or the radial dimension of the bottom of the groove is 0.2-10 mm.

8. The composite sheet according to claim 1, characterized in that: The depth of the groove is 0.01 mm-10 mm, and / or the surface roughness of the metal substrate is 0.1-3 μm.

9. The composite sheet according to claim 1, characterized in that: The surface of the non-stick structure is configured as a downwardly concave arc surface.

10. The composite sheet according to claim 1, characterized in that: The total surface area of ​​the non-stick structure accounts for 10%-50% of the surface area of ​​the composite sheet.

11. The composite sheet according to any one of claims 1 to 10, characterized in that: The non-stick structure is made of PFA and / or PTFE.

12. The composite sheet according to any one of claims 1 to 10, characterized in that: The coating comprises: A bottom layer, the bottom layer is attached to the metal substrate, and the bottom layer is a metal layer; A transition layer, wherein the transition layer is attached to the bottom layer, the transition layer comprises a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked; The surface layer is attached to the transition layer, and the surface layer is constructed as a columnar nano-crystal structure layer grown by physical vapor deposition.

13. The composite sheet according to claim 12, characterized in that: The bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer.

14. The composite sheet according to claim 12, characterized in that: The first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is different from the first transition layer.

15. The composite sheet according to claim 12, characterized in that: The columnar nanocrystal structure in the surface layer has multiple grains growing in a columnar shape, and the side surfaces of the multiple grains are bonded to each other. When the surface layer is at a predetermined thickness, the top ends of the grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure.

16. The composite sheet according to claim 15, characterized in that The radial size of the grains is 20-80 nm; and / or The predetermined thickness of the surface layer is 100-600 nm.

17. The composite sheet according to claim 12, characterized in that: The surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer.

18. The composite sheet according to claim 12, characterized in that: The surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer, and amorphous copper is coated outside the grains of the columnar nanocrystalline structure.

19. The composite sheet according to claim 12, characterized in that: The surface of the metal substrate includes a first surface located inside the groove and a second surface located outside the groove, and the coating includes a first coating attached to the first surface and a second coating attached to the second surface, wherein the thickness of the second coating is greater than the thickness of the first coating.

20. The composite sheet according to claim 19, characterized in that The thickness of the second coating is 500-5000nm, and / or The thickness of the first coating film is 500-2000nm.

21. A liner, characterized in that: The inner liner is made of the composite sheet according to any one of claims 1-20.

22. A cooking utensil, characterized in that: The cooking utensil comprises the inner pot according to claim 21.

23. A method for manufacturing a composite sheet, characterized in that: The method for manufacturing the composite sheet comprises: A step of preparing a metal substrate, wherein the step of preparing a metal substrate comprises a step of forming grooves, wherein a plurality of grooves are formed by etching the surface of the metal substrate; A physical vapor deposition step, placing the metal substrate in a physical vapor deposition device to deposit a coating on the surface of the metal substrate; The groove filling step is to fill the groove with a fluorine-containing resin to form a non-stick structure.

24. The method for manufacturing a composite sheet according to claim 23, characterized in that: The groove is formed by using one of an electrochemical etching process, a chemical etching process and a laser etching process.

25. The method for manufacturing a composite sheet according to claim 23, characterized in that: The step of preparing the metal substrate also includes a first polishing step after the step of forming the grooves, wherein the metal substrate is processed by mechanical polishing, plasma polishing, magnetic fluid polishing or chemical polishing so that the surface of the metal substrate to be coated has a roughness of 0.1-3 μm.

26. The method for manufacturing a composite sheet according to claim 23, characterized in that: The groove filling step also includes: filling the fluorine-containing resin into the groove using an impregnation process, an injection molding process, an electrostatic spraying process or a compressed air spraying process, and treating the metal substrate at a temperature of 350-450° C. after filling so that the fluorine-containing resin in the groove is leveled and fills the groove.

27. The method for manufacturing a composite sheet according to claim 26, characterized in that: The step of filling the groove further includes a second polishing step: removing the fluorine-containing resin on the metal substrate outside the groove by mechanical polishing to expose the coating outside the groove and make the surface of the non-stick structure lower than the surface of the coating outside the groove.

28. The method for manufacturing a composite sheet according to claim 23, characterized in that: The physical vapor deposition step includes a surface layer deposition step: the surface layer of the coating is grown into a columnar nano-crystal structure by physical vapor deposition.

29. The method for manufacturing a composite sheet according to claim 28, characterized in that: The deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source; The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis; The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening a carbon source and a nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer.

30. The method for manufacturing a composite sheet according to claim 29, characterized in that: The physical vapor deposition step also includes a transition layer deposition step, which is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing the first transition layer and the second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal elements of the first metal target react with the carbon source and the nitrogen source to form the first transition layer, and the metal elements of the second metal target react with the carbon source and the nitrogen source to form the second transition layer.

31. The method for manufacturing a composite sheet according to claim 30, characterized in that: The physical vapor deposition step also includes a bottom layer deposition step, which is located before the transition layer deposition step. The bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing a metal bottom layer on the surface to be deposited of the metal substrate.

32. The method for manufacturing a composite sheet according to claim 29, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The surface layer deposition step also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, and applying a bias voltage of 140-160V to the metal substrate during deposition.

33. The method for manufacturing a composite sheet according to claim 30, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The step of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260° C., setting the volume ratio of nitrogen gas to acetylene gas to 1:1.8 to 1:2.2, and applying a bias voltage of 140-160V to the metal substrate during deposition.

34. The method for manufacturing a composite sheet according to claim 31, characterized in that: The bottom layer deposition step also includes: setting the temperature of the deposition furnace to 200-450° C., glow cleaning the metal substrate for 3-7 minutes before deposition, and applying a bias voltage of 50-250V to the metal substrate during deposition.